O Gênero requerimento na perspectiva sociorretórica: análise da produção de graduandos no ambiente acadêmico-administrativo da UFRN - Souza, Eliane Cristina Alves de (2013)
In administrative settings of public institutions, many activities are conducted through writing practices. Concerning this, writing is always connected to an activity we intend to perform. Among those practices, the genre request consists of an instrument through which the requirer addresses to an institution in order to request something under the support of legislation. Considering our work experience in a public institution of higher education, we elected - as object of our research - the genre request produced by undergraduates within the administrative domain of the Federal University of Rio Grande do Norte (UFRN) due to its importance in this context. For this, the theoretical framework adopted refers to the socio-rethorical conception of genre studies, which understands the genre as forms as rhetorically typified action (MILLER, 2009a; SWALES, 1990; BAZERMAN, 2009). Regarding methodology, it is a research associated to a qualitative approach (BODGAN; BIKLEN, 1994; CHIZZOTTI, 2010) whose discussion inserts into the field of Applied Linguistics. The data were generated from samples of requests and their users replies in questionnaires, interviews and verbal protocols of writing. The data analysis is based on the ethnographic methods of genre analysis postulated by Devitt, Reiff and Bawarshi (apud JOHNS et al., 2006). These analyses indicated that the requests are not always fully accomplished due to a lack of comprehension about the genre and its rhetorical situation on the part of the producers. It must probably happen - among other reasons - because these students may not have understood that several factors, such as: context, audience and purpose, affect the text production. We believe that one possibility to make the practice of this genre more efficient is to develop a more simple and practical way of elaborating requests, taking the needs imposed by the rhetorical situation as a basis